Analisis intensity-duration-frequency (idf) dan depth-area-duration (dad) di Pulau Bali - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Rainfall is the most important input component in the hydrologic process. Rainfall characteristics, which are intensity (I), duration (1), depth (d), and frequency. Intensity that is related to duration and frequency can be expressed by Intensity-Duration-Frequency (IDF) curve, on the other hand the maximum depth-duration values for various area can be expressed by Depth-Area-Duration (DAD) curve. In this IDF study, hourly rainfall depth was calculated by frequency analysis, that was started by determining the hourly maximum mean rainfall, followed by calculated statistical parameter to choose the best distribution. Intensity could be calculated by three empirical formulas. The formula was chosen by mean of the least standard deviation. In the DAD study for single storm centers, the isohyet are assumed to be the boundaries of individual areas. Then each areal rainfall was calculated. The total rainfall was distributed by adding rainfall duration in series (commonly 6 hours). If it has been done, the data that showed duration division of the mean rainfall for different area would be obtained. Maximum depth-duration values computed for various areas were plotted on a semilog paper and an enveloping curve may be drawn for each duration. The results of this study indicated that the Pearson type III distribution fit to most of data, but the relationship in the intensity and duration curve had intensity formula with different constants, depended on frequency. The maximum mean depth for 6 hours, I2 hours, 18 hours and 24 hours duration for 100 km' area are 113 mm, 124 mm, 143 mm and 164 mm respectively.